2015
DOI: 10.1155/2015/568502
|View full text |Cite
|
Sign up to set email alerts
|

Application and Progress of Combined Mesenchymal Stem Cell Transplantation in the Treatment of Ischemic Cardiomyopathy

Abstract: Treatment of ischemic cardiomyopathy caused by myocardial infarction (MI) using mesenchymal stem cell (MSC) transplantation is a widely researched field, with promising clinical application. However, the low survival rate of transplanted cells has a severe impact on treatment outcome. Currently, research is focused on investigating the strategy of combining genetic engineering, tissue engineering materials, and drug/hypoxia preconditioning to improve ischemic cardiomyopathy treatment outcome using MSC transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…These results confirmed that the GFs within the PRP effect and stimulate BMSCs [60,61]. Some studies showed that the efficacy of MSCs therapies is frequently restricted due to two factors, i.e., the decreased survival capacity of the transplanted cells due to the harsh acidic, hypoxic, and avascular microenvironment at the lesion site, and the absence of control over their differentiation into the damaged tissues [62,63]. Thus, since GFs such as IGF, TGF-β, and VEGF present in platelets can stimulate BMSCs proliferation, reduce apoptosis and chromosomal instability, delay the appearance of senescent features, and enhance bone mineralization, the use of PRP in association with BMSCs may help to overcome the limit linked to the efficacy of MSCs therapies [25,[32][33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 64%
“…These results confirmed that the GFs within the PRP effect and stimulate BMSCs [60,61]. Some studies showed that the efficacy of MSCs therapies is frequently restricted due to two factors, i.e., the decreased survival capacity of the transplanted cells due to the harsh acidic, hypoxic, and avascular microenvironment at the lesion site, and the absence of control over their differentiation into the damaged tissues [62,63]. Thus, since GFs such as IGF, TGF-β, and VEGF present in platelets can stimulate BMSCs proliferation, reduce apoptosis and chromosomal instability, delay the appearance of senescent features, and enhance bone mineralization, the use of PRP in association with BMSCs may help to overcome the limit linked to the efficacy of MSCs therapies [25,[32][33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 64%
“…However, many disadvantages of co‐culture with MSCs, such as inconvenient operation, high cost, low effectiveness, and potential cross‐contamination have limited its clinical application. Recently, the trophic effects of MSC‐secreted bioactive molecules, including exosomes for injured cells, have been demonstrated, especially in hypoxic and apoptotic areas . MSC‐derived exosomes have emerged as an attractive and safe approach for regenerative medicine applications .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the trophic effects of MSC-secreted bioactive molecules, including exosomes for injured cells, have been demonstrated, especially in hypoxic and apoptotic areas. 21 MSC-derived exosomes have emerged as an attractive and safe approach for regenerative medicine applications. 22 Relatively, few studies have focused on MSCs' protective effects in hypoxia-induced damage of islets, and the aforementioned studies showed that MSCs protected the islets against oxidative stress-mediated cell death, 20 but the mechanism for the protective role of MSCs in islets' anti-hypoxic process is still vague.…”
mentioning
confidence: 99%
“…The therapeutic potential of MSCs for cardiac repair is limited, partly due to their low survival rate within the ischemic myocardial microenvironment into which they are introduced ( 8 , 9 ). Hypoxia and serum deprivation, imitating the ischemic engraftment environment, induce the apoptosis of MSCs ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a randomized control trial ( 4 ) and meta-analyses ( 5 , 6 ) have demonstrated that improvement of cardiac function resulting from MSCs transplantation is limited. One major limiting factor in MSCs transplantation therapy is the low survival rate of the transplanted cells ( 7 , 8 ). This is thought to be due to local inflammatory reactions, ischemia and hypoxia ( 9 ).…”
Section: Introductionmentioning
confidence: 99%